Alisher Navoi’s attitude to "green space" - Hayitov, Shavkat (FILOLOGIYA UFQLARI JURNALI, 2024)
Abstract. Life, Independence encourages a person to think in a new way. Not only natural sciences, but also social sciences should be involved in determining the prospects for the protection of our mother planet. After all, only a person who has a deep understanding of cultural and historical values cannot be indifferent to nature, the world of animals and plants. He does not act blindly without thinking about the consequences. A generous man looks for ways to use nature’s blessings wisely. In the works of the President of Uzbekistan, Shavkat Mirziyoyev, environmental problems, issues of preservation of the island and mother nature are deeply analyzed. In the article, the author tried to study the works of Alisher Navoi based on the essence of the current issue. According to Alisher Navoi, treating animals and plants with indifference and lack of passion is spiritual paralysis. Doing things with lust, attacking nature, sacrificing its miraculous creatures is the spiritual and moral deficiency of a person. According to the principles of humanity and generosity of the great thinker, no matter who works in any field, it is necessary that the feelings of kindness, compassion and mercy shine in his behavior and nature. This is the only way in which a person’s relationship with a person and his relationship with nature will be compatible. Some of the mentioned aspects of the topic are explained in depth in the article.